Structure formation of welded joints in pearlitic steels during friction welding in the superplastic range - Khazanov I. O.; Sovetchenko B. F.; Azarov N. A. Nikolai Antonovich; Trushchenko E. A. (1999, 1999)
В фонде НТБ ТПУ отсутствует